Static aeroelastic response of a rotor blade under internal axial loading - Dibble, R.P.; Woods, B.K.; Titurus, B. (My University, 2017)
Variable speed rotors have the potential to significantly improve the performance of modern rotorcraft if the associated resonance complications can be overcome. One proposed method for resonance avoidance is to employ compressive longitudinal loads to alter the rotor’s dynamic properties. This method has been shown to successfully influence a blade’s dynamic properties but the following research investigates the static aeroelastic behavior of the blade under longitudinal loading. A finite element beam model is used to investigate different methods to represent the tendon loads and determine the impact they would have on the blade’s static behavior. The study demonstrates that the method for modelling tendon load is highly influential. Based on this study, the most representative and practically realisable loading model is selected to be used in further aeroelastic analysis. A loosely coupled aeroelastic beam model is then used to represent a blade with tendon loading. The rotor was trimmed for hover and not loaded beyond its buckling load. This model demonstrates that the out-of-plane and torsional deformation, conditions for vertical trim and required power are negligibly changed in response to the considered tendon loads. These results suggest that it is possible to control the blade dynamic properties without significantly affecting the rotor performance.